Assessing the adequacy of the HL7/LOINC Document Ontology Role axis. (28th October 2014) - Rajamani, Sripriya; Chen, Elizabeth S; Akre, Mari E; Wang, Yan; Melton, Genevieve B
Abstract: The healthcare landscape is changing, driven by innovative care models and the emergence of new roles that are inter-professional in nature. Currently, the HL7/LOINC Document Ontology (DO) aids the use and exchange of clinical documents using a multi-axis structure of document attributes for Kind of Document, Setting, Role, Subject Matter Domain, and Type of Service . In this study, the adequacy of the Role axis for representing the type of author documenting care was assessed. Experts used a master list of 220 values created from seven resources and established mapping guidelines. Baseline certification, licensure, and didactic training were identified as key parameters that define roles and hence often need to be pre-coordinated. DO was inadequate in representing 82% of roles, and this gap was primarily due to lack of granularity in DO. Next steps include refinement of the proposed schema for the Role axis and dissemination within the larger standards community.